Editorial (English) - Mota, Maurício (REVISTA QUAESTIO IURIS, 2016)
DOI: 10.12957/rqi.2016.26350 Editorial for vol. 09-4 (2016) The Journal Quaestio Iuris, classified by MEC / CAPES as Qualis A2, Law, now quarterly, in this volume 09, number 03, is pleased to inform all its readers that our Journal was included, on September 2016, in the European Reference Index for the Humanities and the Social Sciences (ERIH PLUS). The purpose of this Index is to increase the overall visibility of high quality research in the humanities and social sciences throughout Europe and to facilitate access to research journals published in all European languages. The ERIH PLUS index covers the disciplines of the humanities and social sciences. The new benchmark is called ERIH PLUS, to indicate that the list has been extended to also include social science disciplines. It is maintained and operated by the Norwegian Center for Research Data - NSD. [...]